2021
DOI: 10.3390/genes12030457
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA (de)Methylation Positively Impacts Seed Germination during Seed Development under Heat Stress

Abstract: Seed development needs the coordination of multiple molecular mechanisms to promote correct tissue development, seed filling, and the acquisition of germination capacity, desiccation tolerance, longevity, and dormancy. Heat stress can negatively impact these processes and upon the increase of global mean temperatures, global food security is threatened. Here, we explored the impact of heat stress on seed physiology, morphology, gene expression, and methylation on three stages of seed development. Notably, Arab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 125 publications
(162 reference statements)
1
16
0
Order By: Relevance
“…For example, the LTR-copia-type retrotransposon ONSEN in Arabidopsis is activated by heat stress [46]. DMRs were identified in both gene sequences and promoter regions under both mild heat stress and severe heat stress, as well as in mitochondrial DNA in Arabidopsis [47].…”
Section: Dna Methylation and High Temperature Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the LTR-copia-type retrotransposon ONSEN in Arabidopsis is activated by heat stress [46]. DMRs were identified in both gene sequences and promoter regions under both mild heat stress and severe heat stress, as well as in mitochondrial DNA in Arabidopsis [47].…”
Section: Dna Methylation and High Temperature Stressmentioning
confidence: 99%
“…It was observed that DNA demethylation caused by the ROS1 gene could impair seed germination by affecting the expression of germination-related genes. On the other hand, under severe heat stress, most of the DMRs are located in the promoters and gene sequences of germination-related genes [47].…”
Section: Dna Methylation and High Temperature Stressmentioning
confidence: 99%
“…This demonstrated that the active demethylation process was triggered by HS (Korotko et al, 2021). DNA demethylation has also been linked to seed germination regulation during HS (Malabarba et al, 2021). The above results indicate that active DNA demethylation maintained by dMTases is a crucial process involved in various biological processes, including thermal stress regulation in plants.…”
Section: Introductionmentioning
confidence: 67%
“…RdDM can not only maintain long-term genome stability by inhibiting transposable elements but also ensure plants’ life activities under stress conditions by regulating gene expression ( Rymen et al, 2020 ; Guo et al, 2021 ). High temperature stress usually promotes RdDM ( Singh et al, 2021 ), which inhibits the expression of ROS1 gene due to hypermethylation and affects seed germination ( Malabarba et al, 2021 ). The slowdown of life activities may be beneficial to tolerate high temperature environments.…”
Section: Srna Functionsmentioning
confidence: 99%